2005
DOI: 10.1038/sj.ejcn.1602304
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the ZENITH study and summary of baseline results

Abstract: Zinc is known to be essential for a great number of biochemical activities and physiological and cognitive functions. The objective of Zenith study was to investigate the effects of Zn, as a nutritional supplement, on psychological and behavioural factors and on surrogate markers that are indicative of trends towards better health in order to evaluate the need for dietary recommendations specific to the studied population. We report in this paper the summary of baseline results obtained before Zn supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(12 reference statements)
2
6
0
Order By: Relevance
“…Reports on vitamin D deficiency in the elderly (Coudray et al, 2005, Annweiler et al, 2010, Annweiler et al, 2012) is extended in the present study where we show that aged animals are deficient in the active form of vitamin D, 1, α25-dihydroxyvitamin D3. The age-related deficiency in vitamin D demonstrated here may be due to decrease production and/or increase metabolic clearance rate because of the high levels of 24-hydroxylase, enzyme that metabolize vitamin D, seen in the elderly [reviewed in (Tuohimaa et al, 2009)].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Reports on vitamin D deficiency in the elderly (Coudray et al, 2005, Annweiler et al, 2010, Annweiler et al, 2012) is extended in the present study where we show that aged animals are deficient in the active form of vitamin D, 1, α25-dihydroxyvitamin D3. The age-related deficiency in vitamin D demonstrated here may be due to decrease production and/or increase metabolic clearance rate because of the high levels of 24-hydroxylase, enzyme that metabolize vitamin D, seen in the elderly [reviewed in (Tuohimaa et al, 2009)].…”
Section: Discussionsupporting
confidence: 65%
“…One of the hormones gaining increasing support as a therapeutic agent to provide neuroprotection in the aging brain is vitamin D. The prevalence of chronic low serum vitamin D concentration in the elderly is estimated to be 50–80% (Nesby-O'Dell et al, 2002, Coudray et al, 2005). More recently, a meta-analysis report shows that vitamin D concentration is even lower in patients with Alzheimer's disease when compared to age-matched controls (Annweiler et al, 2013).…”
mentioning
confidence: 99%
“…Recently, it has been shown that zinc might play an important role for behavioural and mental function, antioxidant system and metabolism, especially in elderly . Other studies have shown that zinc plays a beneficial effect in terms of reducing adverse psychological conditions Coudray et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The study design parameters of the multi-centre ZENITH study have been reported in detail previously (Coudray et al, 2005;Polito et al, 2005;Simpson et al, 2005). The present study investigated the baseline association between serum 25(OH)D and nonverbal tests of cognitive function within these subjects.…”
Section: Designmentioning
confidence: 99%